Qualitative Study on Perpetrator of Child Sexual Violence with the Symbolic Interaction Theory Approach - Affierni, Siti Indriyanti; Nafikadini, Iken; Rokhmah, Dewi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Based on data from the Jember Resort Police (Polres), the highest case of violence against children is sexual violence. The purpose of this research was to analyze the forms of sexual behavior in perpetrators of child sexual violence. This research was a qualitative research with a case study approach, with purposive technique to 7 perpetrators. Credibility was done by testing source triangulation to additional informants, namely wife behavior and triangulation techniques using observation. Most of the events occurred in the perpetrator’s house. Most perpetrators used symbols to commit sexual violence to children with verbal cues and invitations. Most had more than one experience of marriage and other one had not married. There were perpetrators who had risky behaviors that often watched porn videos and had sex with commercial sex workers. Most of the perpetrators had a problem of harmony with their partners. Besides pedophiles, abnormal sexual behavior carried out on victims was incest. The victims were stepchildren who have quiet and weak characters.